In-situ Fracture Stimulation: A State of the Art Review - G. Langlois; Mario Karfakis (International Society of Explosives Engineers, 2009)
Well stimulation is the process by which any production well, whether for production (extraction), storage (injection) or deep interaction (remediation, monitoring, etc) can be made or stimulated to flow at higher levels. This stimulation is driven by active methods to increase the permeability in the near-well environment and create a larger zone of communication between a well and the reservoir it services. Well stimulation is a crucial aspect of well completion and reservoir engineering and is a subject of careful pre-drilling planning. In many modern industrial endeavors the effectiveness of well stimulation is often critical to economic viability. Because of the broad impact of well engineering on several large industries (petroleum and natural gas extraction and storage, geothermal power, groundwater monitoring, extraction and management, environmental remediation, mining and minerals extraction, etc.) changes in the state of the art in well engineering and well stimulation can affect the capabilities of very diverse and disparate industries. This paper is an effort to communicate the status and effectiveness of current practice and technology in well stimulation. The intention being that effective communication of progress can spur innovation in industries that require well stimulation but are removed from immediate communication of technological or practical improvement.